2007
DOI: 10.1155/2007/138245
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Chronic Hepatitis C: Consensus Guidelines

Abstract: Since the last consensus conference on the management of chronic viral hepatitis, a number of studies looking at modifications of the standard course of treatment have been published. These changes have been sufficiently substantive to warrant review to determine whether any changes in the recommended treatment algorithms are needed. A consensus development conference was held in January 2007, and the present document highlights the results of the presentations and discussion about these issues. It reviews the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 91 publications
1
53
0
9
Order By: Relevance
“…Correlation analysis revealed that the percentage of CD158b + NK cells significantly positively correlated with serum AST and ALT levels in chronic HCV patients. This agreed with Vidal-Castineira et al [10] and Hui-Fan et al [8].The later explained that the impaired immune response caused by CD158b leads to exaggerated hepatocytes damage by HCV with high liver enzymes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Correlation analysis revealed that the percentage of CD158b + NK cells significantly positively correlated with serum AST and ALT levels in chronic HCV patients. This agreed with Vidal-Castineira et al [10] and Hui-Fan et al [8].The later explained that the impaired immune response caused by CD158b leads to exaggerated hepatocytes damage by HCV with high liver enzymes.…”
Section: Discussionsupporting
confidence: 89%
“…They were anti-HCV antibody positive and had detectable serum level of HCV RNA by PCR for at least 6 months [10].…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Although more data and experience is needed to establish definite protocols in genotypes 4, 5 & 6 cases, current evidence suggests treating them as genotype 1 cases. 23 Tables 5 & 6 shown to improve responses in such cases, but it is too premature to recommend it. † The newly recommended week 4 qualitative HCV RNA assay helps modify the duration of the therapy based on viral kinetics.…”
Section: Relapsersmentioning
confidence: 99%
“…60,000IU/week) with an aim to achieve & maintain Hb level of ≥10g/dL (return to the pretreatment level is NOT the aim). 23 2. Another study suggested starting EPO therapy at a lower dose of 4,000IU subcutaneously thrice weekly (12,000IU/week) and then increasing the dose depending upon the response.…”
Section: Ribavirin-induced Hemolytic Anemiamentioning
confidence: 99%
See 1 more Smart Citation